Are comorbidities of patients with adrenal incidentaloma tied to sex? - Puglisi, Soraya; Barač Nekić, Anja; Morelli, Valentina; Alessi, Ylenia; Fosci, Michele; Pani, Angelo; Zibar Tomsic, Karin; Palmieri, Serena; Ferraù, Francesco; Pia, Anna; Chiodini, Iacopo; Kastelan, Darko; et al. (Frontiers in Endocrinology, 2024)
A recent cross-sectional study showed that both comorbidities and mortality in patients with adrenal incidentaloma (AI) are tied to sex. However, few longitudinal studies evaluated the development of arterial hypertension, hyperglycemia, dyslipidemia and bone impairment in patients with AI. The aim of this study is to analyze the impact of sex in the development of these comorbidities during longterm follow-up.We retrospectively evaluated 189 patients (120 females, 69 males) with AI, from four referral centers in Italy and Croatia. Clinical characteristics, comorbidities and cortisol after 1-mg dexamethasone suppression test (1-mg DST) were assessed at baseline and at last follow-up visit (LFUV). Median follow-up was 52 (Interquartile Range 25-86) months.The rates of arterial hypertension and hyperglycemia increased over time both in females (65.8% at baseline versus 77.8% at LFUV, p=0.002; 23.7% at baseline versus 39.6% at LFUV, p<0.001; respectively) and males (58.0% at baseline versus 69.1% at LFUV, p=0.035; 33.8% at baseline versus 54.0% at LFUV, p<0.001; respectively). Patients were stratified in two groups using 1.8 µg/dl as cut-off of cortisol following 1-mg DST: nonfunctional adrenal tumors (NFAT) and tumors with mild autonomous cortisol secretion (MACS).In the NFAT group (99 patients, females 62.6%), at baseline, we did not observe any difference in clinical characteristics and comorbidities between males and females. At LFUV, males showed a higher frequency of hyperglycemia than females (57.6% versus 33.9%, p=0.03).In the MACS group (89 patients, females 64.0%), at baseline, the prevalence of hypertension, hyperglycemia and dyslipidemia was similar between sexes, despite females were younger (60, years; p=0.01). Moreover, females presented higher rates of bone impairment (89.3% versus 54.5%, p=0.02) than males. At LFUV, a similar sex-related pattern was observed.Patients with AI frequently develop arterial hypertension and hyperglycemia and should be periodically checked for these comorbidities, regardless of sex. In patients with MACS, the lack of difference between sexes in the frequency of cardiometabolic comorbidities despite that females are younger, and the higher frequency of bone impairment in females, suggest a sex-specific effect of cortisol.